من الوثيقة إلى النص: قراءة نقدية في آليات اشتغال المختار كرفاع على مصادر التاريخ الليبي (Comprehensive Journal of Science, 2024)
This study contributes to advancing critical reading in Libyan historical scholarship and expanding the thematic and methodological scope of national historiography. Using the works of Mukhtar Karfa‘ as a case study—specifically Russian Archive and Libya Al-musawwara magazine. the research applies a discourse-analytic approach to examine these texts as literary narratives with distinct discursive structures. The study analyzes how Karfa‘ employed these sources to reconstruct national memory and navigated the tensions between the independent Russian discourse and the censored Libyan discourse under fascist rule. Findings indicate that while Karfa‘ offers a rigorous and coherent treatment of Russian sources, his reading of Libya Illustrated reflects a patriotic, evaluative stance oscillating between critique and accommodation, with a relative underemphasis on colonial complexities. Despite this, his work constitutes a valuable contribution to debates on resistance and complicity in Libyan historiography
Keywords: Sources of Libyan history- Russian Archive- Libya Al-musawwara- Mukhtar Karfa- National memory- Literary Narrative- Discourse Analysis- Resistance and Complicity